Ruined - Vaughn, Sarah (First Second Books, 2023)
For fans of Bridgerton comes a Regency-era romance graphic novel about the unexpected passion that blooms from a marriage of convenience. The whole town is whispering about how Catherine Benson lost her virtue, though they can never agree on the details. Was it in the public garden? Or a moving carriage? Only a truly desperate man would want her now -- and that's exactly what Andrew Davener is. His family's estate is in disrepair, but Catherine's sizeable dowry could set it to rights. After the two wed, Catherine finds herself inexplicably drawn to Andrew. But could falling in love with her husband tear her marriage apart? In this richly detailed Regency romance, duty and passion collide in a slow-burn tale of intertwined fates.